Case report: Pacemaker lost capture after acute myocardial infarction in a patient with left circumflex coronary artery occlusion - Wu, Zhihong; Tang, Jianjun; Zhu, Qingyi; Hu, Lin; Liu, Zhenjiang; Li, Xuping; Liu, Qiming; Zhou, Shenghua; Chen, Mingxian (Frontiers in Cardiovascular Medicine, 2022)
A 71-year-old female with a dual-chamber pacemaker presented to our hospital complaining of repeated chest pain. She was diagnosed with unstable angina. On day 7, the patient suddenly suffered cardiopulmonary arrest due to an inferior ST segment elevation myocardial infarction (STEMI). Pacemaker lost capture was suspected and was later confirmed by a pacemaker check with a high pacing threshold and a low sensing parameter. Emergency coronary angiography revealed that a large filling defect remained due to an extensive thrombus in the proximal left circumflex (LCX) with thrombolysis in myocardial infarction (TIMI) grade 2 flow, and then a repeat thrombus aspiration was performed. After reperfusion, the parameters of the right ventricular lead were gradually returned. We conclude that the loss of the right ventricular lead pacing occurred in this case of acute coronary syndrome (ACS) induced by an LCX thrombus due to an LCX supplying the right ventricular septal.